2016
DOI: 10.1111/jon.12344
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Brain Lesion Volume Change in Multiple Sclerosis by Subtraction of Magnetic Resonance Images

Abstract: Use of the subtraction algorithm leads to improved reliability and lower operator fatigue in clinical trials and studies of the natural history of MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Our results are in accordance with the literature in which different optimized reading techniques have been compared with scrolling through images, as in subtraction techniques 7,9,11,18,19 or with semiautomated 12 or automated 8,10 assistive software plat- forms. These methods have shown improvement in detecting new lesions and reducing radiologists' false-negative errors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are in accordance with the literature in which different optimized reading techniques have been compared with scrolling through images, as in subtraction techniques 7,9,11,18,19 or with semiautomated 12 or automated 8,10 assistive software plat- forms. These methods have shown improvement in detecting new lesions and reducing radiologists' false-negative errors.…”
Section: Discussionsupporting
confidence: 91%
“…A few studies have shown that methods such as subtraction or registration could improve the detection of new HST2 lesions, but these approaches to imaging may not be practical in many clinical environments. [7][8][9][10][11][12] The purpose of our study was to evaluate the efficacy of an automated coregistration-fusion (CF) approach during follow-up for patients with MS. tion of Helsinki (institutional review board 2016-A00896-45). Signed informed consent was obtained from all subjects.…”
mentioning
confidence: 99%
“…Since detection of CEL is always highly rater dependent, it has been suggested to use subtraction imaging to increase sensitivity in lesion detection, especially for lesion with only subtle contrast enhancement. [ 23 26 ] However, automatically processed image registration is not provided by all vendors or workstations on-the-fly. Even if available it still has its limitations and subtraction without prior registration is prone to motion artefacts and might lead to a number of false positive results ( Fig 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…The method is described in detail elsewhere 11 and is illustrated in Fig 1. Briefly, input images are registered to a common frame of reference at the average position of all input images. Then, radiofrequency bias field variations are modeled as a smoothly varying polynomial function; then, individual registered images are corrected by pixel-wise division by the modeled field.…”
Section: Registration and Subtractionmentioning
confidence: 99%